The Effects Of The Fertil Verde Fertilizer On The Growth And Yield Of Chili Pepper (capsicum Annuum L) In Southern Algeria - Ghemam Amara, Djilani; Kherraz, Khaled; Alia, Zeid; Chamsa, Ahmed Khalifa; Laouedj, Hacene; Senoussi, Mohammad Mourad (جامعة الوادي - University of Eloued, 2020)
A field experiment was conducted on a private farm in El Oued State of Algeria to study the efficiency of using Fertil Verde as a fertilizer by foliar spry on hot pepper seedlings. The treatment by Fertil Verde increased all growth. The increase was significant in the number of main and secondary stems, the size of the leaves, and the weight of the dry leaves. While, the weight of the wet leaves did not significantly increase. Moreover, the use of Fertil Verde has led to a significant increase in the yield qualities of the plant: the weight and shape of the fruits, fresh yield of the plant, the content of pigment, and the size of the plant. Thus, the combination of fertilizing is common and Fertil Verde is a promising low-cost option in the production of high yields.
Keywords: Chili pepper; Capsicum annuum; Fertil Verde; weight of fruit; vegetative growth; yield.